Deaf in AI: AI language technologies and the erosion of linguistic rights - De Meulder, Maartje (Language and Law / Linguagem e Direito, 2026)
This paper examines the interplay of AI language technologies, sign language interpreting, and linguistic access, focusing on how these developments risk eroding hard-won linguistic rights of deaf communities. While AI tools promise innovation and resilience, they also perpetuate biases, reinforce technoableism, and exacerbate inequalities through systemic and design flaws. The historical privileging of sign language interpreting as the dominant framework for access influences AI’s development and deployment, often sidelining deaf languaging practices and creating new hierarchies of accessibility. These dynamics threaten to replace linguistic autonomy with technological subordination, particularly for marginalized deaf users. Drawing on Deaf Studies, Sign Language Interpreting Studies, and crip technoscience, this paper critiques the framing of AI as a substitute for interpreters and highlights its broader implications for access frameworks. It calls for deaf-led approaches to ensure AI fosters equitable, ethical, and trustworthy accessibility practices, rather than undermining the linguistic and social rights of deaf communities.